Positive interactions between corals and damselfish increase coral resistance to temperature stress - Shantz, Andrew; Ladd, Mark; Ezzat, Leila; Schmitt, Russell; Holbrook, Sally; Vega Thurber, Rebecca; Burkepile, Deron; Schmeltzer, Emily (Dryad, 2022)
By the century’s end, many tropical seas will reach temperatures exceeding
most coral species’ thermal tolerance on an annual basis. The persistence
of corals in these regions will therefore depend on their abilities to
tolerate recurrent thermal stress. Although ecologists have long
recognized that positive interspecific interactions can ameliorate
environmental stress to expand the realized niche of plants and animals,
coral bleaching studies have largely overlooked how interactions with
community members outside of the coral holobiont shape the bleaching
response. Here, we subjected a common coral, Pocillopora grandis, to 10
days of thermal stress in aquaria with- and without the damselfish
Dascyllus flavicaudus (yellowtail dascyllus), which commonly shelter
within these corals, to examine how interactions with damselfish impacted
coral thermal tolerance. Corals often benefit from nutrients excreted by
animals they interact with and prior to thermal stress, corals grown with
damselfish showed improved photophysiology (Fv/Fm) and developed larger
endosymbiont populations. When exposed to thermal stress, corals with fish
performed as well as corals maintained at ambient temperatures without
fish. In contrast, corals exposed to thermal stress without fish
experienced photophysiological impairment, a more than 50% decline in
endosymbiont density, and a 36% decrease in tissue protein content. By the
end of the experiment, thermal stress caused average calcification rates
to decrease by over 80% when damselfish were absent but increase nearly
25% when damselfish were present. Our study indicates that
damselfish-derived nutrients can increase coral thermal tolerance and are
consistent with the Stress Gradient Hypothesis, which predicts that
positive interactions become increasingly important for structuring
communities as environmental stress increases. Because warming of just a
few degrees can exceed corals’ temperature tolerance to trigger bleaching
and mortality, positive interactions could play a critical role in
maintaining some coral species in warming regions until climate change is
aggressively addressed.
To assess how fishes influenced coral physiology and thermal tolerance, we
measured the dark-adapted quantum yield, symbiont density, and tissue
protein content of coral fragments throughout a thermal stress experiment.
Measurements were taken on Day 1 when the corals were brought to shore,
prior to acclimation with damselfish, and on Day 14 after two weeks of
acclimation with or without damselfish present. Temperatures were then
increased in half of the tanks over 24 hours to 30.5°C, and subsequent
measurements made on Days 17, 20, and 24, corresponding to 3, 6, and 10
days of temperature stress, respectively. After completing our
measurements on Day 24, we lowered the temperatures in the heated aquaria
back to 27.5°C over 24 hours and collected final measurements on Day 34,
after 10 days of recovery. At each sampling time point, we haphazardly
selected one fragment from each tank for sampling. We used PAM fluorometry
to measure the maximum dark-adapted quantum yield of PSII (Fv/Fm) after 30
minutes of dark acclimation. After taking fluorescence measurements, we
removed the tissue from each fragment with a waterpik and centrifuged the
resulting tissue slurry at 5,000xG for 5 minutes to separate the coral
tissue and Symbiodineaceae. Symbiont pellets were resuspended in 1 ml
filtered seawater while the coral tissue was rapidly frozen by submersing
the sample tubes in -80°C acetone for 5 minutes, followed by storage at
-80°C for protein analysis. Symbiont density of each fragment was
calculated from eight replicate counts on a Neubauer hemocytometer and
normalized to the fragment's skeletal surface area, as determined by
wax dipping (Stimson and Kinzie, 1991). To determine protein content of
coral tissue, we lyophilized the frozen coral tissue at -80°C to a
constant weight. Next, the freeze-dried tissue was homogenized and diluted
in 0.5 ml of PBS buffer, vortexed for 20 min, and immersed in a sonicating
water bath for an additional 20 min. The solution was then filtered
through a 0.2 μm filter and the resulting supernatant analyzed on a
Millipore Direct Detect infrared spectrometer against a bovine serum
albumin standard (EMD Millipore, Billerica MA, USA). Finally, we measured
differences in coral calcification rates, as determined by changes in
buoyant weight (Davies 1989), for the fragments collected on the final day
of thermal stress and after the 10-day recovery period. To determine how
the yellowtail dascyllus impacted nutrient levels we measured ammonium
(NH4+), nitrate (NO3-), and soluble reactive phosphorus (SRP) in every
aquarium approximately weekly throughout the experiment.
# Positive interactions between corals and damselfish increase coral
resistance to temperature stress
[https://doi.org/10.5061/dryad.zpc866t9t](https://doi.org/10.5061/dryad.zpc866t9t) Supplemental data for “Positive Interactions Between Corals and Damselfish Increase Coral Resistance to Temperature Stress”. Data uploaded include coral physiological measurements with descriptors on first page of excel sheet and nutrient measurement data with descriptors on first page of excel sheet. Any questions regarding this data should be directed to ashantz@FSU.edu ##
Keywords: FOS: Biological sciences; General Environmental Science; Ecology; Environmental chemistry; Global and Planetary Change